PERANCANGAN AR DAN VR BERBASIS ANDROID UNTUK MEDIA PROMOSI PENGEMBANG PERUMAHAN PT. GRIYA PANTURA MANDIRI KENDAL - Yuli Fitrianto; Muhammad Khoiril Anaam (STEKOM PRESS, 2020)
Augmented Reality (AR) and Virtual Reality (VR) which are one of the top ten strategic technology trends for 2019 and continue to be developed massively in this 2020, have been widely applied in various mobile applications by many companies in this industrial revolution era 4.0. AR can be applied to help the promotion for housing developers where users can see the 3-dimensional shape of the types of houses offered, while VR allows users to explore each part of the house in a virtual 3D. Pre-existing brochures are used as markers for this application to work, so that AR and VR applications can be a complement to promotional media. The design method used in this paper is Research and Development (RnD). Salespeople can offer types of houses to prospective customers without having to print multiple brochures, but with just one brochure and one android smartphone to present, so the promotion costs are more efficient. Keywords: AR, VR, house.